(untitled) (LEARNing Landscapes, 2024)
While it began with a variety of narrative representations of writing personal experiences, since Ellis (2004; Bochner & Ellis, 2016), evocative, performative, and creative nonfiction forms of storying have coalesced to form contemporary autoethnography. For over a decade, Canadian arts education researchers have blazed trails to employ those forms of autoethnography as “learning stories” (Carr, 2001; Carr & Lee, 2012) to study teaching and learning practices in a variety of school and community educational contexts. Learning stories enable educators to reveal teaching and learning experiences that cannot be represented by, or communicated through, other research forms. The present inquiry, which begins with the story of an early childhood educator, is rooted in the fusion of evocative autoethnography and learning stories with arts-based research, particularly a/r/tography.